A Review of HCL-Doped- Polyaniline, Tio2 Nanoparticles and P-Toluene Sulfonic Acid Doped Polyaniline:Titanium Dioxide Nanocomposite: The Impact of Nanoparticle Dispersion on Polymer Reinforced Nanocomposites (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The initial results on polymer reinforcement of nanoparticles are incompatible with the improvements in the resulting nanocomposites ' fundamental thermal and mechanical properties. It soon became apparent that a multitude of parameters affected the overall performance of nanocomposites such as the dispersion and distribution of nanoparticles, the transfer of load from nanoparticles to matrix, the geometric arrangement of nanoparticles, the nano-scale mechanical reaction of nanoparticles, the formation and properties of interphase polymers as well as the chemical modification of nanoparticles. Originally, the most important factor was the dispersion of nanoparticles, where increasing the clustering of nanoparticles contributed to better dispersion and improved the contact area between polymer and nanoparticles. With improved processing methods leading to better distributed systems, the rise in nanocomposite modules is now more clear, but there is still more or less elusive growth in strength and durability.